Analisis Penerapan Akuntansi pada Usaha Kos di Desa Secang Samban: Studi tentang Pengelolaan Keuangan, Pencatatan Transaksi, dan Pelaporan Keuangan untuk Meningkatkan Efisiensi Bisnis - Manao, Irene Jeniart; Hendrajaya, Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the application of accounting in boarding house businesses in Secang Samban Village and identify the obstacles faced by business owners in financial management. The problem focuses on financial records that are still done manually and the minimal use of technology in managing cash flow. In order to approach this problem, theoretical references from managerial accounting and accounting information systems are used. Data were collected through observation, interviews, and documentation with descriptive qualitative research methods. The results of the study indicate that the majority of boarding house business owners have not implemented a systematic accounting system, so that financial records are less than optimal. The main factors that are obstacles are limited understanding of accounting, lack of time to do routine records, and low adoption of technology in bookkeeping. This study concludes that basic accounting education and training, as well as the use of digital bookkeeping applications, can be a solution to increasing the effectiveness of financial records and supporting more professional and sustainable boarding house business management.